Analysis of the Ideal-Point Model of Attitude toward Orange Juice Products - Ujang Sumarwan (Media Gizi dan Keluarga, 2001)
The purpose of this study was to examine the consumers¡¦ attitudes toward orange juice products of two different brands. The organoleptic tests were conducted for collecting the data from respondents who were purposively selected in Bogor. The respondents were asked to evaluate six attributes of orange juice products on a 5 point scale, based on the Ideal-Point Model of Attitude. The results showed that of the six attributes, the orange content perceived to be the most important attribute. The Ideal-Point Attitude Model scores for BUAVITA brands were lowe than that of ABC Brands, indicating that respondents were more favorable toward BUAVITA dan ABC orange juice